Bronchodilator Use for Acute Chest Syndrome Among Large Pediatric Hospitals in North America. (December 2018) - Kopel, Lianne S.; Klings, Elizabeth S.; Monuteaux, Michael C.; Gaffin, Jonathan M.; Heeney, Matthew M.; Phipatanakul, Wanda
The utility of bronchodilators to treat acute chest syndrome (ACS) in patients with sickle cell disease is unknown. Our objectives were to examine the variability in bronchodilator use for ACS among pediatric hospitals contributing to a large database and to examine the relationship between bronchodilator use and length of stay (LOS) and mortality. Between 2005 and 2011, bronchodilators were used during 6812/11 328 hospitalizations (60.1%) and use varied from 0.0% to 97.0% (median = 46.0%, interquartile range = 37.0% to 74.0%). Median LOS was 4 days, and interquartile range was 2 to 6 days. Bronchodilator use was associated with a 13.2% increase in LOS (95% confidence interval = 9.2% to 17.3%, P < .001). However, in the subgroup with asthma, bronchodilator use was associated with a 17.9% decrease in LOS (95% confidence interval = 1.7% to 31.4%, P = .03). There is wide variability in bronchodilator use for ACS, and it has variable association with LOS, depending on comorbid asthma. Prospective trials are needed to evaluate bronchodilators for ACS.